2011
DOI: 10.1016/s0929-6646(11)60078-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Inspiratory Muscle Strength Training Effects Between Older Subjects With and Without Chronic Obstructive Pulmonary Disease

Abstract: IMST increases maximal inspiratory pressure, relieves dyspnea and improves health-related quality of life in older adults. IMST especially improves functional status in subjects without COPD. IMST benefits subjects with COPD and those without COPD. Therefore, IMST as a treatment tool is not confined to patients with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 31 publications
3
24
0
1
Order By: Relevance
“…Moreover, diaphragm fast-fatigable fibers are activated only with the highest imposed loads and expulsive reflexes [48], [78]. Clinically, IMST of patients has been shown to increase strength, reduce dyspnea, and facilitate weaning from MV [7], [79][81]. We speculate that fast-fiber hypertrophy could be particularly beneficial to patients with respiratory muscle weakness and cough dysfunction, which are highly predictive of ventilatory failure [82][85].…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, diaphragm fast-fatigable fibers are activated only with the highest imposed loads and expulsive reflexes [48], [78]. Clinically, IMST of patients has been shown to increase strength, reduce dyspnea, and facilitate weaning from MV [7], [79][81]. We speculate that fast-fiber hypertrophy could be particularly beneficial to patients with respiratory muscle weakness and cough dysfunction, which are highly predictive of ventilatory failure [82][85].…”
Section: Discussionmentioning
confidence: 89%
“…For that, researchers found that PR-IMT devices had an impact on their health status by strengthening their respiratory muscles and improving daily life activities. Regarding applying high intensities of PR-IMT on COPD patients, two studies [19,20] had a sample of nearly 35 subjects; the intensities were highly similar (nearly up to 80% of MIP in both) and applied six weeks training period. Huang et al, [19] the investigators applied daily training twice a day, each session lasts for 15 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding applying high intensities of PR-IMT on COPD patients, two studies [19,20] had a sample of nearly 35 subjects; the intensities were highly similar (nearly up to 80% of MIP in both) and applied six weeks training period. Huang et al, [19] the investigators applied daily training twice a day, each session lasts for 15 minutes. While, Madariaga et al [20] applied five days of training per week.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MIP is indicative of ventilatory capacity 1) and is particularly useful for monitoring inspiratory muscle weakness of patients 2) . However, there is substantial variation in published MIP data [3][4][5] ; furthermore, in Taiwan, people often do not produce the recommended MIP reference values 6) . Most MIP reference values are derived from measurements of Caucasians, and at least 2 studies with large sample sizes 7,8) and other smaller studies 4,5) concluded that there is no ethnic effect on MIP.…”
Section: Introductionmentioning
confidence: 99%